Sustainability & Identity: Bali’s Struggle in the Age of Mass Tourism - Spitz, Christoph (Institute for Research and Community Services Udayana University, 2025)
Bali, renowned for its rich cultural heritage and scenic landscapes, has emerged as a prominent destination for global tourism, leading to substantial economic advantages. Nonetheless, the swift expansion of mass tourism has introduced numerous challenges, especially concerning architectural integrity. Traditional Balinese architecture, which is profoundly anchored in the principles of Tri Hita Karana highlighting the necessity for balance among humanity, nature, and the divine now encounters mounting pressures from the arrival of Western-style commercial constructions. These contemporary constructions frequently emphasize financial gain and visual appeal at the expense of sustainability and cultural authenticity, resulting in ecological harm, the forced relocation of local populations, and the deterioration of Bali's distinctive cultural heritage. This study investigates the effects of mass tourism on Balinese architecture, examining the extent to which traditional principles are supplanted by globalized design practices. It employs the framework of Critical Regionalism to suggest solutions that incorporate local materials, cultural knowledge, and environmental factors into contemporary tourism infrastructure. By integrating Tri Hita Karana, this paper promotes a comprehensive approach to tourism development that reconciles the island’s economic advancement with the conservation of its spiritual and ecological values. The research contends that the advancement of sustainable tourism in Bali should transcend immediate financial benefits and concentrate on enduring strategies that honor the island’s cultural heritage and ecological boundaries. It utilizes comparative cases from Southeast Asia to illustrate how Bali can adopt a contemporary yet culturally rooted perspective on architecture, thereby guaranteeing that the island continues to be a sustainable and culturally vibrant locale for forthcoming generations.